Navigating Globalization: Reforming Islamic Education for the 21st Century - Hajar, Andi (Yayasan Sinergi Kawula Muda, 2024)
Islamic education is at a pivotal crossroads as globalization accelerates the need for comprehensive educational reform across Muslim-majority societies. This narrative review investigates how Islamic educational institutions are adapting to global influences while maintaining fidelity to religious values. Employing a structured literature review of sources from Scopus, Google Scholar, and PubMed, this study analyzes academic works published over the past 15 years. Keyword combinations including